NEWS IN THE ONLINE INSURANCE SYSTEM - Muhammadaliyev Zuhriddin Khabibullo ogli (Galaxy International Interdisciplinary Research Journal, 2021)
This article discusses the innovations in the insurance system, the use of which will help mankind to facilitate various tasks.